Technology transfer, intellectual property, and the fight for the soul of WHO. - Melissa Barber (PLOS Global Public Health)
Debates over the scope, terms, and governance of technology transfer-the sharing of essential technical information, know-how, and materials needed to manufacture a health product-are prominent and controversial in international health diplomacy. These debates have become focal points in recent contentious negotiations to amend the International Health Regulations (IHR) and draft a global Pandemic Agreement. While some countries advocate for automatic or compulsory mechanisms to facilitate access to health technologies, especially in times of crisis, others oppose legal frameworks that mandate non-voluntary participation by the pharmaceutical industry. Also at stake are questions of institutional mandate: the United States has amplified calls by industry that pandemic technology transfer policy should be the domain of the World Trade Organization (WTO) instead of the World Health Organization (WHO). This essay offers a counternarrative to claims that WHO is overstepping its historic role in global governance. Far from being a contemporary development, technology transfer was at the heart of WHO's work at its founding. WHO's early failure to secure antibiotic technology transfer in the face of US opposition led to its first major crisis, prompting the withdrawal of several member states. In response, WHO embarked in the 1950s on a visionary programme to establish a global network of non-profit, state-run drug manufacturers and scientists committed to the free exchange of knowledge. This ambitious initiative has been largely forgotten, excluded even from WHO's self-published accounts of historical technology transfer work. In the context of ongoing pandemic governance negotiations and the nascent mRNA hub program, remembering the lost vision of global solidarity embodied in WHO's midcentury technology transfer program offers a glimpse into an alternate path we might still chart, one where access to medicines is not bound by the logic of enforcing scarcity to maximize profit, and the right to health is a global responsibility.